Searching for new young stars in the northern hemisphere: the Pisces Moving Group - Binks, Alex S.; Jeffries, Robin D.; Ward, Jacob L. (Arxiv, 2017)
Using the kinematically unbiased technique described in Binks, Jeffries & Maxted (2015), we present optical spectra for a further 122 rapidly-rotating (rotation periods < 6 days), X-ray active FGK stars, selected from the SuperWASP survey. We identify 17 new examples of young, probably single stars with ages of < 200 Myr and provide additional evidence for a new northern hemisphere kinematic association: the Pisces Moving Group (MG). The group consists of 14 lithium-rich G- and K-type stars, that have a dispersion of only $\sim